Jewels of Crafts – Forging Blades, Fletching Arrows, Making Naphtha, and Manufacturing Black Powder – a Persian Manuscript on Warfare - Khorasani, Manouchehr Moshtagh (Tools of war, 2023)
The present article deals with an undated Persian manuscript titled Javāher al-Sanāye’ ﺟﻮﺍﻫﺭﺍﻟﺼﻨﺎﻳﻊ (Jewels of Crafts). Many Persian manuscripts provide invaluable information on weapon-making, forging swords, archery techniques, attacking fortifications, casting cannons and making firearms, and military strategies. Most accounts on making crucible steel are part of books on jewels and stones. In my last book Jewels and Patterned Crucible Steel: Books of Jewels, Stones, and Metals, I provided a translation and annotation of the book Goharnāmeh [Book of Jewels] written by Mohammad ben Mansur for the ruler Uzun Hasan Āq Qoyonlu in the 15th century CE (9th century Hijra). The Goharnāmeh by Ben Mansur describes precious and semi-precious stones, animal products, and metals. An essential part of the book deals with blades and making crucible steel. However, the manuscript Javāher al-Sanāye’ (Jewels of Crafts), which is the topic of this article, is about the transformation of stones and metals. The book describes how the craftsmen made crucible steel and expands on how ironworkers used crucibles for conducting other alchemical processes to change and transform the colour of stones, among other processes. Javāher al-Sanāye’ (Jewels of Crafts) is a gem for war-related topics as it provides invaluable information on how to make crucible steel blades, how to identify and classify swords, how to make the adhesive glue for attaching the blade tang to the handle of the sword, how to make glue for fletching arrows, how to make naphtha (burning material) for attacking fortifications, and how to make the black powder.